A genre analysis of paid obituary announcements in selected Pakistani English newspapers - Chaudhry, Sajid Mahmood (2017)
Newspaper paid obituary announcements are contextualized generic structures with religious and socio-cultural communicative functions. This generic structure reflects differences among people from various social strata to project their social status. The analysis in the Pakistani milieu was conducted due to a lack of studies which explore these announcements to determine local socio-cultural and socio-economic factors which influence their communicative intents. A genre analysis was conducted to determine the communicative purposes, stylistic devices, gender representation, content selection and non-linguistic features of this genre. Data were obtained by describing, investigating and analysing the discourse generic modes. The data comprises 601 printed paid obituaries selected from Pakistani English newspapers; The Dawn and The News International. A total of 30 respondents from various background were interviewed. A methodological framework of Al-Ali in 2005 which was an adapted form of Swales in 1990 moves analysis model, is used as a prototypical. Moves analysis and inductive reasoning lead towards the structural and informational understanding of these announcements. Procedural steps involving trilateral phases: identification, comprehension and validation have been adopted. The findings show a blend of similarities and dissimilarities with the similarly produced genre globally. It was also found that the communicational load of the textual moves of this genre is dependent on the contextualized societal and religious practices, and personalized intentions of the discourse community. The findings of this study could serve as an abstract model of guidance for the professional and unprofessional writers of this genre in Pakistan. It also helps to create awareness towards using appropriate linguistic forms among practitioners of English in Pakistan, and provides a theoretical model for future researches dealing with a similar subject matter